Quantifying Literature: It’s Not All About the Digital (KULT_online, 2020)
Ted Underwood’s Distant Horizons: Digital Evidence and Literary Change sets off for a pacifist mission to reconcile traditional literary studies and distant reading, by recentering the debate around statistical methods borrowed from social sciences, away from buzzwords and polemical statements. In doing so, he makes a case for new discoveries in the field of literary studies that – even though they have been made easier by recent advances in access to digital libraries and machine learning algorithms –  are really mostly based on methods that have been around for at least half a century. Perhaps the biggest strength of Underwood’s newest work is that it could convince even the fiercest traditionalists that quantitative analysis should have its place in literary studies.